Search and Satisficing - Caplin, Andrew; Dean, Mark; Martin, Daniel (American Economic Review, 2011)
Many everyday decisions are made without full examination of all available options, and, as a result, the best available option may be missed. We develop a search-theoretic choice experiment to study the impact of incomplete consideration on the quality of choices. We find that many decisions can be understood using the satisficing model of Herbert Simon (1955): most subjects search sequentially, stopping when a “satisficing” level of reservation utility is realized. We find that reservation utilities and search order respond systematically to changes in the decision making environment. (JEL D03, D12, D83)